The effect of zinc supplementation on collagen of periodontitisrat - Praptiwi, Siti Fatimah Muis Soeharyo Hadisaputro, Suryono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: Zinc,cofactors of DNA-and RNA-polymerase, having great role in tissue heal-ing. In periodontitis, collagen type 1 the main fiberconstituting periodontal structure is des-troyed and be the main cause of lost of teeth among adult in Indonesia. Zndeficiency is still a nutritional problem. The aim of the study is to obtain the influence of 500 pg Zn supplementation (Zn,1and 200 pg (Zn2)per day for 7 days to periodontal collagen of Periodontitis (PI rat through histologic feature. Method: inthe experimental study with factorial design, 29 adult male Wistar rat were used. Subjects were grouped simple randomly into 6 i.e Healthy (H)at the start, Hatthe end, p, P+Te-tracycline IT), ,P + T+ Zn" and P+ T+ Zn2.Subject other than Hgroups were induced periodontitisby Porphyromonasgingivalisbacteria. Zn concentration was measured by AAS Flame, Periodontal tissue was stained with Mallory,s. T test and ANOVAwas used to analyse difference between mean of Znconcentration of groups studies. Result: There were similarity in the feature of groups H at the start, Hat the end, and P+ T+ Zn" in sense of regularity, length, and solidity of collagen. P group had irregular, and short collagen. Groups of P+ T with shorter collagen, had similarity to Health at the end. P+ T+ Zn2with shorter collagen similar to P+T+ Znl. There was significant difference inZn concentrat-ion between Hat the end and Pgroup. Nosignificant differencies among Zn concentrations of Psubject groups. Great variety of Zn concentration found among subjects of groups prob-ably were the cause of absence of difference, although means of the Zn concentration values depicted it. Conclusion: Zn supplementation dosage 500 pg/day given to periodontitis rat beside Tetra-cycline, gives better effect to collagen structure compared to 200 pg/day.